Developing Vocabulary Digital Pocket Book to Online Business and Marketing (OBM) Students at Vocational High School Level - Widiarini; Zidni, Zidni Fima Khoiro Sholihah; Mubarok, Tyas Alhim (English Education:Journal of English Teaching and Research, 2023)
This research is based on an analysis of vocational high school students’ needs majoring in Online Business and Marketing (OBM). It was found that the students faced difficulties in mastering vocabulary, in which vocabulary is a fundamental and important component for communication. Ideally the vocabulary that should be mastered is related to their major study. In order to overcome this problem, this research aims to develop learning media in the form of a Digital Vocabulary Pocket Book (DVPB) to teach vocabulary. This research used Research and Development (R&D) research method using the ADDIE model which was developed in 1996 by Dick & Carry, which includes 5 stages of research they are: Analysis, Design, Development, Implementation, and Evaluation. The results of this study are ; the feasibility value from the expert validation of the language aspect is 90%, media aspects 89%, and material aspects 89%. Moreover the 30 students’ responses toward Digital Vocabulary Pocket Book (DVPB) reach 94%. In conclusion, Pocket Book dictionary can be used to help students in learning vocabulary.